Brain electrical activity from encoding to retrieval while maintaining and manipulating information in working memory. Issue 8 (14th September 2019) - Román-López, Talía V.; Caballero-Sánchez, Ulises; Cisneros-Luna, Silvia; Franco-Rodríguez, J. Antonio; Méndez-Díaz, Mónica; Prospéro-García, Oscar; Ruiz-Contreras, Alejandra E.
ABSTRACT: Differences between working memory maintenance (Mt) and manipulation (Mp) have been studied, mostly in the absence of stimuli ( delay period ); encoding and retrieval phases have been less explored. The present study assessed differences between Mt and Mp, by means of event-related potentials (ERPs) and event-related synchronisation (ERS) and desynchronisation (ERD) for theta, alpha and beta bands at: encoding, delay period and retrieval ; using a delayed-match to sample task (DMST). Twenty-six young volunteers solved two DMST conditions (one for Mt and one for Mp). Higher behavioural accuracy for Mt than for Mp was observed. At encoding, higher amplitude for Mt at posterior regions to N1, P2 and P3 components were observed. In the delay period, differences in ERP components and frontal theta ERD were observed. Meanwhile, at retrieval, P3 amplitude and latency, as well as the theta band were modulated by both process (Mt or Mp) and type of trial (target or non-target stimuli). These findings mainly suggest different attentional implications at encoding, differences at the delay period related with task difficulty, and differential retrieval for Mt or Mp dependent on the process which the information comes from, suggesting that Mt and Mp differ at the very beginning of the processing.